2015
DOI: 10.1007/s10584-015-1579-8
|View full text |Cite
|
Sign up to set email alerts
|

Attribution of yield change for rice-wheat rotation system in China to climate change, cultivars and agronomic management in the past three decades

Abstract: Using the detailed field experiment data from 1981 to 2009 at four representative agro-meteorological experiment stations in China, along with the Agricultural Production System Simulator (APSIM) rice-wheat model, we evaluated the impact of sowing/transplanting date on phenology and yield of rice-wheat rotation system (RWRS). We also disentangled the contributions of climate change, modern cultivars, sowing/ transplanting density and fertilization management, as well as changes in each climate variables, to yi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
39
1
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(45 citation statements)
references
References 21 publications
(30 reference statements)
3
39
1
2
Order By: Relevance
“…Here we assumed that climate change did not modify the tendencies of vegetation covers, but dominated the inter-annual variation of vegetation density. Renewal of crop cultivars, applications of synthetic fertilizer and irrigation, as well as conservancy tillage and nitrogen deposition all contribute to the crop and/or natural productivity improvements (Yu et al, 2012;Bai et al, 2016;Piao et al, 2015). National statistical records of grain yields on county scale showed a rapid increase from 1980 to 1990 and a moderate increase in the 2000s.…”
Section: Effects Of Agronomic Practice Technique Advancement and Othmentioning
confidence: 99%
See 1 more Smart Citation
“…Here we assumed that climate change did not modify the tendencies of vegetation covers, but dominated the inter-annual variation of vegetation density. Renewal of crop cultivars, applications of synthetic fertilizer and irrigation, as well as conservancy tillage and nitrogen deposition all contribute to the crop and/or natural productivity improvements (Yu et al, 2012;Bai et al, 2016;Piao et al, 2015). National statistical records of grain yields on county scale showed a rapid increase from 1980 to 1990 and a moderate increase in the 2000s.…”
Section: Effects Of Agronomic Practice Technique Advancement and Othmentioning
confidence: 99%
“…For example, Piao et al (2015) documented that elevated atmospheric CO 2 and nitrogen deposition were the critical contributors to terrestrial greening over China; Baker et al (2010) figured out that climate anomalies in springtime were the most frequent drivers of annual GPP variations in North America; Nayak et al (2013) reported that climate change had a relatively small but significant control (15 %) on the trend of terrestrial net primary production (NPP) over India. In the crop ecosystems, contributions of climate change, cultivar renewal, and agronomic management to change in crop yield have been separated with the crop or statistical models (Yu et al, 2012;Song et al, 2014;Bai et al, 2016;Guo et al, 2014;. The impacts of climate change on crop yield may be positive or negative in different regions, depending on the tendencies of the dominant factors (Ewert et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…For example, earlier sowing dates prolonged the growing period of maize in northeastern China by 4 to 21 days 6 . New cultivars of rice and wheat with higher thermal requirements and later maturity dates that were introduced in China during 1981–2009 expanded their growth season lengths and compensated for the advancement in crop phenology caused by increased temperatures 7,8 . The length of the growing season for cereals such as wheat increased by approximately 10 days in Finland due to a cultivar change 9 .…”
Section: Introductionmentioning
confidence: 99%
“…The direct effects include the implications of higher temperatures and changes in ambient carbon dioxide concentrations on the growth, development, and yield of rice plants [20,21]. Additionally in this category are the impacts of changes in rainfall patterns, humidity, solar radiation, and average wind speeds, which influence rice growth and grain yields [22][23][24][25]. The indirect effects include changes in crop water requirements and in water availability, particularly in areas where rice is irrigated.…”
Section: Climate Change and Rice Productionmentioning
confidence: 99%